Dan Poynter's self-publishing manual how to write, print and sell your own book - Poynter, Dan (Para Publishing, 2006)
In this digital age, self-publishing is an attractive, viable option for many writers — if they only knew where to start. Dan Poynter demystifies the publishing process, breaking it down into an approachable, step-by-step procedure that anyone with a little time and motivation can easily master. From tips for writing more efficiently to shipping the book out the door, this encyclopedic guide covers everything the author/publisher needs to know, including typesetting, layout, and printing; obtaining an ISBN; forming a publishing company; creating effective press kits; getting marketing and promotional advice; printing on demand, downloading books and e-books; getting the book in stores and catalogs; producing profitable spin-offs such as audio and videotapes, excerpts, and foreign-language editions; and much more.